1989
DOI: 10.1016/0042-6989(89)90127-2
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the masking effects of two-dimensional stimuli

Abstract: Ahatraet-Gratings that differ in orientation by as much as 62.5 deg from that of a signal grating raise the signal's threshold by nearly a log unit. The spatial-frequency tuning of the masking effect reaches a maximum slightly below the spatial frequency of the maskers but far from that of any quadratic distortion product. Further, the location of the peak does not depend much on the relative orientation of the signal and maskers thus making it unlikely that the masking effect can be explained in any simple wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…For intermediate orientations (640 to 670 deg), they found that masking was greater for the plaid mask than for the grating mask (''super suppression''), broadly consistent with the scheme in Fig. 1b (see also Derrington & Henning, 1989). Thus, we reasoned that this super suppression might be cortical and might also be revealed by the dichoptic masks here, albeit at a higher mask spatial frequency.…”
Section: An Unexpected Result: Orientation Pooling Is the Same For Mosupporting
confidence: 82%
“…For intermediate orientations (640 to 670 deg), they found that masking was greater for the plaid mask than for the grating mask (''super suppression''), broadly consistent with the scheme in Fig. 1b (see also Derrington & Henning, 1989). Thus, we reasoned that this super suppression might be cortical and might also be revealed by the dichoptic masks here, albeit at a higher mask spatial frequency.…”
Section: An Unexpected Result: Orientation Pooling Is the Same For Mosupporting
confidence: 82%
“…In this instance, masking increased as the noise widened from 0.75 to 1.5 octaves where it reached its peak, and further widening of the noise band led to a reduced masking level. Derrington and Henning 20 have also found maximum masking effects at off-test frequency using luminancedefined grating patterns. They measured orientation and spatial frequency tuning by measuring the detectability of a range of vertically oriented test gratings (from 0.5 to 6 cyc/deg) that were masked by two 3-cyc/deg mask gratings oriented at Ϯ22°, Ϯ45°, and Ϯ67.5°from vertical.…”
Section: Discussionmentioning
confidence: 90%
“…at the simple cell level: Dean, Tolhurst & Walker, 1982;Reid & Shapley, 1988;Tolhurst, Walker, Thompson & Dean, 1980). Even a simple nonlinear transducer function following linear oriented channels may be insufficient to account for spatial pattern masking results (Derrington & Henning, 1989). On the other hand, Jamar and Koenderink (1985) have found that it is possible to use effective spectral (contrast) energy over a broad range of spatial frequency to predict performance at detection of noise gratings, consistent with a linear channels hypothesis.…”
Section: Introductionmentioning
confidence: 80%